Coverage region switching method under earth-fixed footprint mode for LEO satellite constellation - QI Xiaoxin; SONG Baojun; LI Xun (Tongxin xuebao)
In low earth orbit (LEO) satellite constellations, when earth-fixed footprint mode is used, the switching of beams between coverage regions affects the elevation angle of the coverage, which in turn affects the communication quality. A coverage region switching method was proposed to address the coverage region switching problem in earth-fixed footprint mode. Firstly, a coverage region division mechanism was designed to keep the coverage region topology regular. Then, a switching time selection mechanism and a target coverage region selection mechanism were designed with the objective of maximizing the minimum elevation angle of the beams. The proposed method takes the differences between polar and inclined orbit constellations into account and supports both constellations. The OneWeb and Telesat constellations are used as simulation scenarios to validate the proposed method. The simulation results show that the proposed method can effectively improve the minimum elevation angle of the beams, which helps to improve the link quality.